Physicochemical Studies on the Surface of Polyamide 6.6 Fabrics Functionalized by DBD Plasmas Operated at Atmospheric and Sub-Atmospheric Pressures - Nascimento, Larissa; Gasi, Fernando; Landers, Richard [UNESP]; Silva Sobrinho, Argemiro da; Aragao, Eduardo; Fraga, Mariana; Petraconi, Gilberto; Chiappim, William; Pessoa, Rodrigo (Mdpi, 2020)
This work proposes the use of a dielectric barrier discharge (DBD) reactor operating at atmospheric pressure (AP) using air and sub-atmospheric pressure (SAP) using air or argon to treat polyamide 6.6 (PA6.6) fabrics. Here, plasma dosages corresponding to 37.5 kW center dot min center dot m(-2)for AP and 7.5 kW center dot min center dot m(-2)for SAP in air or argon were used. The hydrophilicity aging effect property of untreated and DBD-treated PA6.6 samples was evaluated from the apparent contact angle. The surface changes in physical microstructure were studied by field emission scanning electron microscopy (FE-SEM). To prove the changes in chemical functional groups in the fibers, Fourier transform infrared spectroscopy (FTIR) was used, and the change in surface bonds was evaluated by energy dispersive X-ray spectroscopy (EDS) and X-ray photoelectron spectroscopy (XPS). In addition, the whiteness effect was investigated by the color spectrophotometry (Datacolor) technique. The results showed that the increase in surface roughness by the SAP DBD treatment contributed to a decrease in and maintenance of the hydrophilicity of PA6.6 fabrics for longer. The SAP DBD in air treatment promoted an enhancement of the aging effect with a low plasma dosage (5-fold reduction compared with AP DBD treatment). Finally, the SAP DBD treatment using argon functionalizes the fabric surface more efficiently than DBD treatments in air.
Keywords: atmospheric plasma; sub-atmospheric plasma; dielectric barrier discharge; polyamide 6; 6; surface modification; wettability; whiteness